(untitled) (Research, Society and Development, 2021)
Objective: to know the scientific production on health practices in the prevention of sexually transmitted infections. Methods: described study, of the type integrative review. The Virtual Health Library (VHL) was used for data collection between December 2018 and January 2019. The data included were complete articles and available in full, in Portuguese, published between 2013 and 2018. Results: 12 articles were analyzed, the information was divided into two categories according to the type of strategy employed in prevention practices, namely: assistance actions and preventive educational actions. Schools present themselves as the scenario for carrying out preventive actions and adolescents are the main target of interventions. It was noted the difficulty of health and education professionals in addressing issues related to sexual health and sexuality, the need for continuing education for professionals. The workshops and group activities have a positive impact in the fight against infections, however, the stigma and taboo still permeate the subject. Conclusions: assistance and educational actions must be carried out together. It is salutary that there is continuous qualification and improvement of professionals, organization of health services and incorporation of intersectoral actions, in addition to actions in the community that promote the perception of risk for sexually transmitted infections, with the encouragement of safe practices for health in all countries. groups and age groups.